Cloud computing – CLOUD 2018 : 11th International Conference, held as part of the Services Conference Federation, SCF 2018, Seattle, WA, USA, June 25-30, 2018, Proceedings /: 11th International Conference, held as part of the Services Conference Federation, SCF 2018, Seattle, WA, USA, June 25-30, 2018, Proceedings. (2018) - Unknown
No abstract available